Determination of frequency, causes and preventability of adverse events in the pediatric ward a IPS Quindio 2014 (Revista de Investigaciones Universidad del Quindío, 2016)
Patient safety involves legal and ethical responsibility of the health care provider, in order to perform this profession in a competitive and safe way, with self-determination and self-regulation of its actions. (1) Objective: to determine the frequency, causes, and avoidability of adverse events in the pediatrics department of a HSP in the department of Quindío, in 2014. Methodology: a quantitative, retrospective, crosssectional study was performed with a census sampling method; an analysis with SPSS V17 was performed, Univariate: in which the sociodemographic characteristics, the percentages of adverse events, their causes and bivariate analysis were identified: to make comparisons between groups, 2 by 2 tables were made; to evaluate categorical variables Chi2 test and Fischer's exact test were performed with an alpha level of 0.05, which determined the statistical significance. Conclusions: It was found that adverse events in the pediatrics department were more common in infants (60%) and female preschool children (40%), 64.3% of adverse events occurring in this service are attributed to causes related to direct patients care; 85.7% of the cases shows flaws in human and administrative barriers which predispose occurrence of adverse events directly. 73.3% of the population belongs to the subsidized regime of the adverse events presented 64.3%, of the adverse events that occurred in the period of time evaluated are preventable causes.
Keywords: Adverse event; Pediatrics